ANALISIS PENGARUH SERVQUAL TERHADAP KEPUASAN PELANGGAN PT. AMARTHA MANUNGGAL PRIMA CABANG PANGKALPINANG (STUDI KASUS PADA ID EXPRESS CABANG PANGKALPINANG) - Anne, Angeline Putri; Zamhari; Oktalina, Gayatria (Jurnal Ilmiah Niaga Bisnis Elektronik, 2023)
The research method uses a quantitative descriptive approach. The data collected by distributing questionnaires to 93 respondents in this study were Pangkalpinang ID Express customers. The sample is determined by using purposive sampling technique. Data analysis used Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Test, Simultaneous Test (F Test), and Partial Test (t Test) which were processed with JASP. The results show (1) Tangibles had no partial effect on customer satisfaction with a significance value of 0.815 > 0.05 and a tcount value of 0.235 < a ttable value of 1.66235. (2) Reliability has a partial effect on customer satisfaction with a significance value of 0.040 <0.05 and a tcount of 2.090 > of a ttable value of 1.66235. (3) Responsiveness has a partial effect on customer satisfaction with a significance value of <.001 <0.05 and a tcount of 4.431 > of a ttable value of 1.66235. (4) Assurance has no partial effect on customer satisfaction with a significance value of 0.124 > of 0.05 and a tcount of 1.552 235 < of a ttable value of 1.66235. (5) Empathy has a partial effect on customer satisfaction with a significance value of <.001 <0.05 and a tcount of 4.693 > of a ttable value of 1.66235. (6) Tangibles, Reliability, Responsiveness, Assurance, Empathy simultaneously influence customer satisfaction with a significance value of 0.001 <0.05 and fcount value 52.205 > than ftable value 2.71.